HPLC 를 이용한 가는장구채 추출물의 Isoscoparin 분석법 개발 - 권진관; Jin Gwan Kwon; 서찬곤; Changon Seo; 정연우; Yeon Woo Jung; 최용문; Yongmun Choi; 신현탁; Hyun Tak Shin; 정수영; Su Young Jung; et al. (大韓化粧品學會誌, 2021)
본 연구는 가는장구채(Silene seoulensis) 추출물을 기능성 화장품소재로 개발하기 위해 isoscoparin을 지표성분으로 선정하고, 품질관리를 위해 high performance liquid chromatography (HPLC)를 이용하여 분석법을 개발하였다. 분석용 칼럼은 Unison US-C 18 을, 이동상은 0.05% (v/v) trifluoroacetic acid (TFA)와 메탄올을 사용하여 컬럼 온도는 35 ℃ 에서 유속 1.0 mL/min 로 검출파장은 330 nm에서 검출하였다. International conference on harmonization (ICH) 가이드라인(version 4, 2005)을 근거로 하여 특이성, 직선성, 정밀성, 정확성, 검출한계 및 정량한계를 분석하여 분석방법을 검증하였다. 분석결과, 검출한계 및 정량한계는 0.02 및 0.07 mg/mL로 나타났으며, 검량곡선은 상관계수 값이 0.99988로 양호한 직선성을 보였고 정밀성 분석결과도 0.46% 이하로 확인되었다. 또한, 회수율은 99.10 ~ 101.61% 범위로 정확성이 있음을 확인하였다. 따라서, 본 분석법은 가는장구채 추출물 지표성분의 분석법으로 적합한 시험법임이 검증되었다. In this study, isoscoparin was selected as an indicator component to develop Silene seoulensis extract as a functional cosmetic material, and we developed an analysis method using high performance liquid chromatography (HPLC) for quality control. HPLC was performed on a Unison US-C 18 with a gradient elution of 0.05% (v/v) trifluoroacetic acid (TFA) and methanol at a flow rate of 1.0 mL/min at 35 ℃, and the detection wavelength was 330 nm. The HPLC method was performed in accordance with the international conference on harmonization (ICH) guideline (version 4, 2005) of analytical procedures with respect to specificity, precision, accuracy, and linearity. The limits of detection and quantitation were 0.02 and 0.07 mg/mL respectively. Calibration curves showed good linearity (R2 > 0.99988), and the precision of analysis was satisfied (less than 0.46%). In addition, the recovery rate was in the range of 99.10 to 101.61%, it was shown to be accurate. This result indicated that the established HPLC method is very useful for the determination of marker compounds in Silene seoulensis extracts.